A first‐generation microsatellite linkage map of the ruff. Issue 14 (24th October 2013) - Farrell, Lindsay L.; Burke, Terry; Slate, Jon; Lank, David B.
Abstract A linkage map of the ruff (Philomachus pugnax) genome was constructed based on segregation analysis of 58 microsatellite loci from 381 captive‐bred individuals spanning fourteen breeding years and comprising 64 families. Twenty‐eight of the markers were resolved into seven linkage groups and five single marker loci, homologous to known chicken (Gallus gallus) and zebra finch (Taeniopygia guttata) chromosomes. Linkage groups range from 10.1 to 488.7 cM in length and covered a total map distance of 641.6 cM, corresponding to an estimated 30–35% coverage of the ruff genome, with a mean spacing of 22.9 cM between loci. Through comparative mapping, we are able to assign linkage groups Ppu1, Ppu2, Ppu6, Ppu7, Ppu10, Ppu13, and PpuZ to chromosomes and identify several intrachromosomal rearrangements between the homologs of chicken, zebra finch, and ruff microsatellite loci. This is the first linkage map created in the ruff and is a major step toward providing genomic resources for this enigmatic species. It will provide an essential framework for mapping of phenotypically and behaviorally important loci in the ruff.